Konstruksi Penataan Daerah dan Model Pembagian Urusan Pemerintahan - Sherlock Halmes Lekipiouw (SASI, 2020)
Regional arrangement and distribution model of governmental affairs. The purpose of this research is to provide clarity regarding the legal interpretation of the formulation of norms in regional government laws. Research methods The research method uses normative research through a conceptual approach and a statue approach. The results showed that the development of decentralization into a state administration system had an impact on local government institutions, one of which was the distribution pattern of government affairs. Thus, comparing the distribution of functions is not possible without the overall decentralized institutional framework developed by a country. From this, a comprehensive framework of decentralization institutions and local government is needed. It also does not rule out the possibility for a region to propose governmental affairs that become its specialty, both on a provincial and regional scale. The concept of division of functions is carried out dynamically, where regions can carry out real government affairs (needed and in accordance with regional capacities). It should be possible for districts / cities to propose governmental affairs that are needed or not needed; who can or cannot be arrested. Decentralization can only work if it is based on a number of preconditions, namely a capable and effective central government. Therefore, it is necessary to review various regulations that are not in line with the principle of broadest autonomy.